Application of micro X-ray diffraction to investigate the reaction products formed by the alkali–silica reaction in concrete structures. (January 2016) - Dähn, R.; Arakcheeva, A.; Schaub, Ph.; Pattison, P.; Chapuis, G.; Grolimund, D.; Wieland, E.; Leemann, A.
Abstract: Alkali–silica reaction (ASR) is one of the most important deterioration mechanisms in concrete leading to substantial damages of structures worldwide. Synchrotron-based micro-X-ray diffraction (micro-XRD) was employed to characterize the mineral phases formed in micro-cracks of concrete aggregates as a consequence of ASR. This high spatial resolution technique enables to directly gain structural information on ASR products formed in a 40-year old motorway bridge damaged due to ASR. Micro-X-ray-fluorescence was applied on thin sections to locate the reaction products formed in veins within concrete aggregates. Micro-XRD pattern were collected at selected points of interest along a vein by rotating the sample. Rietveld refinement determined the structure of the ASR product consisting of a new layered framework similar to mountainite and rhodesite. It is conceivable that understanding the structure of the ASR product may help developing new technical treatments inhibiting ASR.